A STUDY ON THE EFFECTS OF HOUSING POLICIES ON HOUSING COOPERATION IN TURKEY AND THE ROLE OF HOUSING COOPERATION ON HOUSING PRODUCTION (Third Sector Social Economic Review, 2017)
Humankind has been in tendency of finding secure shelters to preserve himself from external factors in addition to the basic biological needs like eating, drinking and reproduction for centuries. These shelters have changed and developed according to the production form and needs based on the nature. So, housing in terms of modernism can be identified as a physical place for individual’s sheltering and the places which help for socialization and have the sense of belonging. Thanks to the industrial revolution in Europe, the migration from country to the cities caused the increase of and the problem of housing population in the cities. This event made the problem of housing as a universal problem in 19th century, and became a triggering role for the states’ housing policies. Housing policy can be defined as the whole constitutional, legal and organisational measurements for eliminating the housing needs of the state.  With the proclamation of Republic in Turkey, the housing problem arose depending on population growth, migration and rapid urbanisation, and the state had to follow some housing policies for solution. Several public organisations were authorised for determining these policies and implementations. The other organization for taking an important role for housing production was housing cooperation besides public organisations and private sector. Housing cooperation can be defined as economic and social institutions that appeal to poor people as part of help and solidarity and based on volunteering. Housing cooperation had adhered to Turkish Trade Act until Cooperation Law numbered 1163 in 1969. With the help of this law, the foundation of upper organisations, the attendance of local managements and social security institutions to cooperation became available. Also, it was observed that housing cooperation was supported and promoted by the state on the subjects like obtaining credit, tax reduction and immunity. These practices that can be seen as a reflection of housing policies in terms of the state caused the housing cooperation to increase in number in 1970s and grew to its highest range of 36.3% in 1986. On the other hand, from 2000 to today it is observed that the share of housing cooperation on the housing production has been decreased. The share of housing cooperation in the sector is about 2.5% in 2016. It is thought that this decrease is originated from the changes happened against the housing policies.This study aims to analyse the positive and negative effects of housing policies on housing cooperation which isn’t independent from the housing policies and which is associated to the non-governmental organisations.
Keywords: Housing; Housing policies; Housing Cooperation; Housing Production; Housing problem.